Factors that affects employee engagement amongst employees in human capital management, Petronas Twin Towers, KLCC / Nuril Amalina Ahmad Hanafiah - Ahmad Hanafiah, Nuril Amalina (Faculty of Business and Management, 2014)
Due to globalization of the organization, Employee Engagement is something that needs to take seriously. Employee Engagement will effect on the effectiveness and performance of the each organizations. In the presence of Organizational Commitment, Job Content and Culture of Support will lead to Employee Engagement. This paper is to analyze the relationship among these variables. Data were obtained from 108 employees in Human Capital Management, PETRONAS Twin Towers, KLCC. Pearson Correlation and Multiple Regression Analysis have been carried out separately for each of these engagement variables to investigate the relationship towards them. The finding indicates that all variables (Organizational Commitment, Job Content and Culture of Support) have significant contribution towards Employee Engagement.